2008
DOI: 10.5194/npg-15-1-2008
|View full text |Cite
|
Sign up to set email alerts
|

A model for aperiodicity in earthquakes

Abstract: Abstract.Conditions under which a single oscillator model coupled with Dieterich-Ruina's rate and state dependent friction exhibits chaotic dynamics is studied. Properties of spring-block models are discussed. The parameter values of the system are explored and the corresponding numerical solutions presented. Bifurcation analysis is performed to determine the bifurcations and stability of stationary solutions and we find that the system undergoes a Hopf bifurcation to a periodic orbit. This periodic orbit then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 39 publications
4
88
2
Order By: Relevance
“…This type of state evolution law was used in numerical simulations by YOSHIDA and KATO (2003), HE (2003) and ERICKSON et al (2008). Because the sliding behaviour and the condition for the occurrence of unstable slip are different for the two types of state evolution law (MARONE 1998;RANJITH and RICE 1999), the simulation results in the present study cannot be directly compared with those using the slip type of the state evolution law.…”
Section: Modelmentioning
confidence: 42%
See 1 more Smart Citation
“…This type of state evolution law was used in numerical simulations by YOSHIDA and KATO (2003), HE (2003) and ERICKSON et al (2008). Because the sliding behaviour and the condition for the occurrence of unstable slip are different for the two types of state evolution law (MARONE 1998;RANJITH and RICE 1999), the simulation results in the present study cannot be directly compared with those using the slip type of the state evolution law.…”
Section: Modelmentioning
confidence: 42%
“…A singledegree-of-freedom spring-block model has been used with rate-and state-dependent friction to investigate the details of the sliding behaviour and stability in the system concerned (RICE and TSE 1986;GU and WONG 1991). ERICKSON et al (2008) showed that a singledegree-of-freedom spring-block model exhibits complex slip behaviour when the steady-state friction shows extremely velocity weakening. MA and HE (2001) used a two-degree-of-freedom springblock model with a rate-and state-dependent friction law to examine complex sliding processes, and found that period-doubling bifurcation occurred for some friction parameters, where large events and small events occurred alternately.…”
Section: Introductionmentioning
confidence: 99%
“…Along those lines, it should be noted that period-doubling bifurcation cascades have been reported for systems similar to the one studied here (e.g. [61,62]). However, from a practical point of view, measurements of friction are generally rather noisy, and it is far from clear whether complicated transitions, including chaos, could be reliably detected.…”
Section: Case Studies (A) Rate-and-state Friction and The Mass-springmentioning
confidence: 94%
“…Change in the friction was studied as a function of displacement and velocity at a variation of the stiffness coefficient in the rate-and-state equation. A similar approach was implemented by Erickson et al (2008); they examined an appearance of chaotic solutions in the one-parameter velocitydependent friction equation.…”
Section: Introductionmentioning
confidence: 99%